Adropin inhibited tilapia hepatic glucose output and triglyceride accumulation via AMPK activation. Issue 2 (August 2020) - Zhang, Chaoyi; Zhang, Qianli; Huang, Zhihong; Jiang, Quan
Abstract : Adropin plays a role in the maintenance of energy homeostasis, insulin resistance prevention, and impaired glucose tolerance. However, the molecular mechanisms by which adropin affects hepatic glucose and lipid metabolism in vitro are not entirely understood. This study intended to examine the roles and underlying mechanisms of adropin in glucose and lipid metabolism in Nile tilapia. In primary cultured tilapia hepatocytes, adropin significantly attenuated oleic acid (OA)-induced glucose output and reduced the activities and mRNA expression of cytosolic phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), which are involved in gluconeogenesis. In contrast, adropin facilitated glucose uptake activity via glucose transporter 1 ( Glut1 ) upregulation in OA-treated hepatocytes. One-week of adropin treatment reduced the hepatic total lipid accumulation in OA-fed tilapia without changes in body weight. Subsequent studies revealed that adropin suppressed OA-induced intracellular triglyceride accumulation and decreased the expression of genes and proteins involved in lipid metabolisms such as sterol regulatory element-binding protein-1c (SREBP-1c), acetyl-CoA carboxylase α (ACCα) and CD36, but upregulated peroxisome proliferator-activated receptor α (PPARα) levels. In parallel studies, however, adropin had no detectable effects on fatty acid-binding protein 4 ( Fabp4 ) and carnitine palmitoyltransferase 1α ( Cpt1α ) mRNA expression. Furthermore, adropin treatment dose-dependently increased the phosphorylation level of AMP-activated protein kinase (AMPK). Suppression of AMPK by compound C or AMPKα1 siRNA blocked adropin-induced decreases in the mature form of SREBP-1c expression, glucose output, and intracellular triglyceride content in OA-treated hepatocytes. These findings suggest that teleost adropin could suppress hepatic gluconeogenesis and triglyceride accumulation via a mechanism dependent on AMPK signalling.